Dynamic simulations of urban policies for sustainable food securitization : dynamics of urban development, agriculture sector growth, and price mechanisms - Montesclaros, Jose Ma. Luis P. (2021)
Global trends show decreasing global food security (measured by the ratio of food supply to demand) over the past years, but the future outcome is not something that can be defined based on statistical trends. Rather, there are non-linear dynamics that will eventually lead to a bouncing up back up of food production. This was uncovered by assessing how the current food insufficiency situation has developed, with the primary lenses of urban development, rural production, and price dynamics. Wages in agriculture have been consistently lower than those in industry and services sectors, leading to increasing migration to cities where the latter sectors are based. This migration has led to decreasing food production, as labor is required to till the agricultural land in rural areas. However, by this same mechanism, food scarcity increases, and the price of food eventually increases. Governments eventually find the need to give priority to ensuring food sufficiency for their constituents, as is the case in many developing countries wherein more funds are allocated for encouraging food production. This leads sequentially to an increase in wages in agriculture, migration back to agricultural jobs, and a bouncing back up of food production. However, the combination of 1) market failures shaping the allocation of resources, 2) investment delays from poor spread of knowledge of appropriate investments, and 3) delays in product delivery from producers to consumers, will prevent this bouncing back up from happening. The sooner these issues are addressed, the better the capability of the market’s price mechanism to mobilize actors. Policy recommendations showed three potential scenarios for the extent of time (in years) under which the urban food insecurity situation will be resolved. The fact that the problem remains to be a persistent one shows that the feedback loops for addressing it are not yet triggered; as such, the price mechanism is not yet functioning properly. The set of policy recommendations, derived from the causal analysis, may be applied to systemically improve the dynamics shaping the future of food security globally and by extension, in urban areas.